New substrate for plant growth based on granite powder and biodegradable geomimetic composites obtained from bentonite-poly(glycerol citrate) - Lerma, Tulio A.; Paradelo, Remigio; Palencia, Manuel (Materials today communications, 2024)
Granite powder (GP) alkaline waste of industrial origin that can provide nutrients for agricultural production. However, due to its high alkalinity it can reduce the availability of Fe and generate chlorosis in plants. In this work, the use of geomimetic composites mixed with GP has been proposed as an eco-friendly plant growth substrate. Thus, bentonite-poly(glycerol citrate) geomimetic composites (BPGC) were synthesized and added to GP. The effect on nutrient leaching, growth of Lolium perenne and physicochemical properties of substrates prepared were assessed. BPGC were synthesized by surface modification of bentonite with (3-aminopropyl)triethoxysilane and followed by polyesterification with glycerol and citric acid. Structural characterization by infrared spectroscopy, magnetic resonance and scanning electron microscopy allowed to verify that structural configuration mimics the structure of soil particles. BPGC showed a thermal degradation from ∼140 °C and a decrease on Tg as clay content in composite is increased. Leaching profiles of substrates produced from GP and BPGC showed the ability of mixture to interact with nutrients and reduce the losses of them, showing a greater tendency for retaining of potassium and phosphorus. Finally, the plant growth experiments showed no trend or relationship between the yield of Lolium perenne and the treatments assayed. Therefore, it is concluded that the addition of BPGC to GP modulated and improved the physicochemical properties of the substrates evidencing its potential application as amendment for the restoration of degraded soils, however, an improvement in the growth of the plants evaluated was not evident. [Display omitted] •Granite powder (GP) is an industrial waste that can provide nutrients for plants.•The use of geomimetic composites mixed with GP has been proposed.•Bentonite-poly(glycerol citrate) geomimetic composites (BPGC) were synthesized.•Structural, functional, leaching experiments and assays with plants were performed.•BPGC and GP mixtures improve the physicochemical properties of plant growth substrates.